Two new species of gill parasites assigned to Protoancylodiscoides (Monogenea, Ancyrocephalidae) from Chrysichthys spp. (Siluriformes, Claroteidae) in River Sanaga (Cameroon) - Bayiha, Etienne D. Bassock; Nack, Jacques; Pariselle, Antoine; Bilong, Charles F. Bilong (Zootaxa, 2016)
Host specimens were sampled in the middle course of the River Sanaga (Cameroon) from January to October 2014. Two new species, Protoancylodiscoides auratum n. sp. from Chrysichthys auratus and Protoancylodiscoides combesi n. sp. from C. auratus, Chrysichthys nigrodigitatus and Chrysichthys longidorsalis, are herein described. These new helminths differ from the congeneric species by the size of the haptoral sclerites, the male copulatory organ length, the diameter and morphology of the vagina. At this stage, the present study suggests that Protoancylodiscoides auratum is oioxenous, while P. combesi is stenoxenous. The two new Protoancylodiscoides species bring to three the number of those parasitizing C. auratus, and to four the number of those described from Chrysichthys spp.